Two-dimensional Dirac nodal loop magnons in collinear antiferromagnets. (21st June 2018) - Owerre, S A
Abstract: We study the nontrivial linear magnon band crossings in the collinear antiferromagnets on the two-dimensional (2D) CaVO lattice, also realized in some iron-based superconductors such as AFe1.6+ x Se2 (A = K, Rb, Cs). It is shown that the combination of space-inversion and time-reversal symmetry ( symmetry) leads to doubly-degenerate eight magnon branches, which cross each other linearly along a one-dimensional loop in the 2D Brillouin zone. We show that the Dirac nodal loops (DNLs) are not present in the collinear ferromagnet on this lattice. Thus, the current 2D antiferromagnetic DNLs are symmetry-protected and they provide a novel platform to search for their analogs in 2D electronic antiferromagnetic systems.